Notes on Early Land Plants Today. 63. Validation of the family Phyllothalliaceae (Pallaviciniales, Jungermanniopsida, Marchantiophyta) - Katagiri, Tomoyuki; Söderström, Lars; Hagborg, Anders; Von Konrat, Matt (Phytotaxa, 2014)
When Hodgson (1964) proposed the new family Phyllothalliaceae together with the initially monotypic genus Phyllothallia Hodgson (1964: 247) based on Phyllothallia nivicola Hodgson (1964: 247), she mentioned “This new family is not a splinter entity from any already recognized family, but is originated to contain a genus which in vegetative characters at least is completely different from any known genus. The characters of the family are those of the genus”. The first sentence specifies the features in which Phyllothalliaceae is different from the other families but not how these features differ and so it does not satisfy the requirement of Art. 38.1(a) for a description/diagnosis (see: Art. 38. 2. Ex. 4). Although Grolle (1972: 216) discussed the validity of the family and considered the second sentence fulfil the requirements for the valid publication, ICN (McNeill et al. 2012) allows a single description/diagnosis for monotypic genus and species only. Hence, the family Phyllothalliaceae lacked a description/diagnosis which was needed when proposed and it has never been validly published until now. In order to be able to use the name in the forthcoming world checklist of Hornworts and Liverworts (Söderström et al., in prep.), the family is validated here. Note that a Latin description is no longer needed under the current ICN (McNeill et al. 2012).